The implementation of NMR techniques for measuring interactions between small organic molecules/inhibitors and enzyme Acetylcholinesterase: a step towards Alzheimer´s control - Urooj, Nazish (Universidade Federal de São Carlos, 2015)
The inhibition of the acetylcholinesterase (AChE) might be an excellent therapy in controlling Alzheimer’s disease as stated by the cholinergic hypothesis. In this context, the inhibitors of AChE, are of medical and commercial paramount interest as therapeutics for Alzheimer’s disease and as pesticides. However, the conformational changes in inhibitors with AChE complex facilitate the rational design of some novel inhibitors with increased potency and specificity. Therefore, solution state NMR is a novel approach that seems to fulfil almost all conditions necessary to investigate the AChE-inhibitor complex. In this perspective, a combined strategy of STD, Tr-NOESY, DOSY, and docking simulations were applied to compare the bindings of four synthetic coumarin derivatives to tacrine for their binding potentials. Intriguingly, one of them (compound 1) was found to have not only the stronger affinity than the control but could bind with three sites. Furthermore, a competition of three inhibitors (gallic acid, 4- methylumbelliferone, and scopoletin) was performed by taking help of the STD NMR experiments. Interestingly, none of them was competing for the some particular binding site. Nevertheless, in titration studies gallic acid was found best based on dissociation constant values. Moreover, an ethyl acetate fraction and its water suspension of the Terminalia Chebula RETZ, fruit extract was studied. Three compounds (4-hydroxycinnamic acid, Ethyl-4-hydroxycinnamate and lupeol) were seen to involve in interaction that were later recognized by 2D NMR and ESI mass techniques. Moreover, for the first time in the Federal University of São Carlos, these NMR methods for the determination of the bound conformation of any inhibitors towards AChE using NMR spectroscopy have been applied.
Implementação de técnicas de RMN para medir interações entre moléculas orgânicas inibidoras da enzima Acetilcolinesterase: um passo para o estudo do Alzheimer
Keywords: Ressonância magnética nuclear; Alzheimer, Doença de; Nuclear magnetic resonance; Alzheimer's disease; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ORGANICA